Subchronic Toxicity of the Ethanolic Extract of Lecaniodiscus cupanioides on Albino Wistar Mice (Mus musculus) - Adeola Michael Oloyede; Bodunrin Ottu; Adebayo Ogunsanwo; Samuel Sobiye; Bolarinwa Kehinde; Catherine Aromolaran; Chinwedu Ogidi; Ekene Okafor (Lorestan University of Medical Sciences, 2021)
Background and Aim: Lecaniodiscus cupanioides has been used in traditional therapies in Nigeria for the management of several ailments. This study investigated its subchronic toxicity. Materials and Methods: 30 mice (20-25g) were placed in three groups of 10 mice. Groups A and B were orally administered 100 and 400 mg/kg of ethanolic extract respectively for 49 days, while group C received distilled water as the control. At expiration of the treatment, the animals were sacrificed to harvest blood and internal organs for hematologic, biochemical, antioxidant and histologic analyses. Results: Hematologic analysis revealed increased monocytes in all the groups. Biochemical and Electrolytes analytes did not show any significant difference. Antioxidant results showed a dose-dependent significant decrease in super oxide dismutase (SOD). Glutathione (GSH) revealed a significant increase in 400mg/kg. No pathology was observed in the heart, but mild toxicity in the kidneys, loss of alveoli architecture in the lungs, inflammation, and congestion of portal triads and central vein in the liver were observed. Increased monocytes observed may depict antibody and anti-infection potentials of the extract. Decreased value of RBC, Hb at higher doses, and mean corpuscular hemoglobin (MCH) at lower doses suggest hemolytic anaemia. Insignificant difference in liver enzymes may suggest extract is not hepatotoxic.  Insignificant increased creatinine and urea implies that the extract is not nephrotoxic. Conclusion: The extract displayed a great potential to inhibit free radicals. It increased the antioxidant defense system and GSH at 400mg/kg. Increased SOD and catalase suggest the upregulation of protein which culminates in the clean-up of free radicals and decreasing oxidative stress, thus protecting tissues from extremely reactive radicals.